Leaf Flavonoid Patterns in the Species of Stemonoporus (Dipterocarpaceae) and Their Taxonomic Significance - Joshi, Kunjani (Journal of Natural History Museum, 2009)
During the chemotaxonomic study of 16 species of Stemonoporus, three flavonoid aglycones (flavonol quercetin, flavonol kaempferol and flavone apigenin) and glycosides (quercetin 3- glucoside, quercetin 3-rutinoside and apigenin 5-glucoside) were isolated while flavonol myricetin, flavone luteolin and proanthcyanidin were not detected in any of the species surveyed. The isolated flavonoids can be used as chemotaxonomic markers. The species of Stemonoporus can be regarded as advanced in flavonoid pattern because of the absence of myricetin and loss of proanthocyanidins. The data of the flavonoid patterns and the outcome of cluster analysis are taxonomically useful to resolve the controversies over the systematic arrangement of the species and suggest the need for a revision of classification of the genus Stemonoporus. Key words: Dipterocarpaceae; Flavonols; Chemotaxonomy; Cluster analysis. Journal of Natural History Museum Vol. 24, 2009 Page: 146-155